Blooming landscapes in the West? German reunification and the price of land. - Raphael Schoettler; Nikolaus Wolf (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
German reunication was a positive market access shock for both East and West Germany. Regions that for 45 years had experienced a decline in population due to their loss in market access following the division of Germany of WWII were most strongly affected by this positive shock. We use an entirely new data set to analyse the effects of German reunication on the value of land in West Germany. We find that regions in the immediate border area experienced a relative rise in land prices compared to regions outside a 100 km radius from the border. At the same time we confirm the absence of a population effect (Redding and Sturm, 2008) even including rural boroughs. We find that land values have adjusted more quickly than population and in some cases even overshot predicted long-run levels within the first decade of reunication. We attribute this finding to the information and expectation component of land prices. Land values incorporate expectations about long- run equilibrium adjustments following reunication more swiftly, but firms and housholds are slower to react due to the costs of relocating. The results are consistent with empirical work on the positive effects of infrastructure projects on land values (Yiu and Wong, 2005; Lai et al., 2007; Duncan, 2011).
Keywords: F15; N14; N94; R12; R30; 330; Economic Integration; Economic History; Regional Economics; Real Estate Markets